A novel haplotype of low-frequency variants in the aldosterone synthase gene among northern Han Chinese with essential hypertension. Issue 39 (September 2017) - Zhang, Hao; Li, Xueyan; Zhou, Li; Zhang, Keyong; Zhang, Qi; Li, Jingping; Wang, Ningning; Jin, Ming; Wu, Nan; Cong, Mingyu; Qiu, Changchun
Abstract : Abstract: Low-frequency variants showed that there is more power to detect risk variants than to detect protective variants in complex diseases. Aldosterone plays an important role in the renin–angiotensin–aldosterone system, and aldosterone synthase catalyzes the speed-controlled steps of aldosterone biosynthesis. Polymorphisms of the aldosterone synthase gene ( CYP11B2 ) have been reported to be associated with essential hypertension (EH). CYP11B2 polymorphisms such as –344T/C, have been extensively reported, but others are less well known. This study aimed to assess the association between human CYP11B2 and EH using a haplotype-based case–control study. A total of 1024 EH patients and 956 normotensive controls, which consist of north Han population peasants, were enrolled. Seven single nucleotide polymorphisms (SNPs) (rs28659182, rs10087214, rs73715282, rs542092383, rs4543, rs28491316, and rs7463212) covering the entire human CYP11B2 gene were genotyped as markers using the MassARRAY system. The major allele G frequency of rs542092383 was found to be risk against hypertension [odds ratio (OR) 3.478, 95% confidence interval (95% CI) 1.407–8.597, P = .004]. The AG genotype frequency of SNP rs542092383 was significantly associated with an increased risk of hypertension (OR 4.513, 95% CI 1.426–14.287, P = .010). In the haplotype-based case–control analysis, the frequency of the T-G-T haplotype was higher for EH patients than for controls (OR 5.729, 95% CI 1.889–17.371, P = .000495). All |D′| values of the seven SNPs were >0.9, and r 2 values for rs28659182- rs10087214-rs28491316-rs7463212 SNPs were >0.8 and showed strong linkage intensity. Haplotype T-G-T may therefore be a useful genetic marker for EH.